Dentofacial traumatic injuries: A survey of knowledge and attitudes among emergency medicine physicians in Turkey. Issue 1 (12th November 2018) - Yigit, Yavuz; Helvacioglu‐Yigit, Dilek; Kan, Bahadir; Ilgen, Cansu; Yilmaz, Serkan
Abstract: Background/Aim: Emergency department (ED) visits for dental issues are mostly related to traumatic injuries. The knowledge of ED physicians about the diagnosis and treatment of dentofacial injuries is crucial for prognosis. The aim of this study was to evaluate the attitude and knowledge as well as education and self‐confidence levels of emergency medicine physicians in ED regarding the diagnosis and treatment of dentofacial traumatic injuries. Material and methods: A total of 109 emergency medicine physicians participated in the study. Participants were residents and specialists who attended a national emergency medicine symposium held in Turkey. A questionnaire was distributed during the symposium relating to general data about physicians, their attitudes, basic knowledge, and confidence levels which were believed to be indicative of their capabilities in managing of traumatic dental and maxillofacial injuries. Results: The questionnaire was answered by 109 physicians who were general practitioners (11%), emergency medicine residents (56.8%), and emergency medicine specialists (32.2%). The most experienced group of physicians were emergency medicine specialists. Regardless of the physicians' titles, dentofacial trauma knowledge levels of ED physicians were found to be insufficient. Having a dentist in the family ( P < 0.01), the duration of emergency service experience ( P = 0.04), and the age of the physicians ( P < 0.001) were significantly related to the knowledge level. Conclusions: The majority of ED physicians had low knowledge regarding the diagnosis and treatment of dentofacial traumatic injuries. There is a need for education during and after medical training for ED physicians to provide appropriate primary management of dentofacial trauma.